2013
DOI: 10.1007/s00464-013-2849-z
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and training in laparoscopic inguinal hernia repair (TAPP): impact of the learning curve on patient outcome

Abstract: Our study demonstrates that the TAPP learning curve of young trainees is only related to operation time. Therefore, TAPP is a safe and reproducible technique when performed by young trainees under the supervision of experienced laparoscopic surgeons. With an adequate program, the technique can be learned quickly, skillfully, and safely when a standardized technique is used. It should be included as a fundamental part of state-of-the-art trainee programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 29 publications
0
27
0
6
Order By: Relevance
“…After introduction of TAPP in 1993 by the chief surgeon firstly he trained and supervised the senior residents and the senior residents trained the residents and the trainees. Teaching and learning as it is used in our department has been published by Bökeler et al [12]. Using this systematic training and supervision the results of trainees and residents are not significantly different except for operation time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…After introduction of TAPP in 1993 by the chief surgeon firstly he trained and supervised the senior residents and the senior residents trained the residents and the trainees. Teaching and learning as it is used in our department has been published by Bökeler et al [12]. Using this systematic training and supervision the results of trainees and residents are not significantly different except for operation time.…”
Section: Discussionmentioning
confidence: 96%
“…However, the length of learning curve is strictly dependent on both standardization of the technique and the educational program used. In institutions presenting a high case load, a strictly standardized technique and a structured educational program, the number of operations a fellow surgeon needs to gain proficiency may be much smaller and will not exceed 50 repairs [12]. Moreover, it is shown that the results of the surgeons in training are not worse compared to those of experienced hernia surgeons provided that adequate supervision is guaranteed [12].…”
Section: Discussionmentioning
confidence: 99%
“…This study was the first to report tangible evidence of improved patient outcomes following surgical simulation. Another study by Bökeler et al [16] validates the need for state of the art training programs to teach and train total awareness of laparoscopic inguinal hernia anatomy among GS residents. In this study, trainees were not allowed to perform a laparoscopic hernia repair until they had met specific preoperative requirements that centered on mastery of groin anatomy from the laparoscopic view.…”
Section: Herniamentioning
confidence: 87%
“…Laparoscopic surgical techniques and endoscopic hernia repair are a part of surgical training offered to registrars in many countries [7]. The outcomes of intensive training based on interactive techniques, surgical simulators and video recording analysis show a lack of differences between the skill level of experienced surgeons, and registrars reveal that the learning curve has been completed [8].…”
Section: Discussionmentioning
confidence: 99%